Aurophilicity‐Mediated Construction of Emissive Porous Molecular Crystals as Versatile Hosts for Liquid and Solid Guests. Issue 3 (16th December 2019) - Seki, Tomohiro; Ida, Kentaro; Sato, Hiroyasu; Aono, Shinji; Sakaki, Shigeyoshi; Ito, Hajime
Abstract: The first examples of porous molecular crystals that are assembled through Au⋅⋅⋅Au interactions of gold complex 1 are here reported along with their exchange properties with respect to their guest components. Single‐crystal X‐ray diffraction (XRD) analyses indicate that the crystal structure of 1 /CH2 Cl2 ⋅pentane is based on cyclic hexamers of 1, which are formed through six Au⋅⋅⋅Au interactions. The packing of these cyclic hexamers affords a porous architecture, in which the one‐dimensional channel segment contains CH2 Cl2 and pentane as guests. These guests can be exchanged through operationally simple methods under retention of the host framework of 1, which furnished 1 /guest complexes with 26 different guests. A single‐crystal XRD analysis of 1 /eicosane, which contains the long linear alkane eicosane ( n ‐C20 H42 ), successfully provided its accurately modeled structure within the porous material. These host–guest complexes show chromic luminescence with both blue‐ and redshifted emissions. Moreover, this porous organometallic material can exhibit luminescent mechanochromism through release of guests. Abstract : The crystalline sample of a gold complex is constructed based on the ring‐shaped hexamer through six aurophilic interactions. Various guest components can be accommodated within the extrinsic pore moiety to tune the solid‐state emission properties.